Quantifying Ecosystem Services and Environmental Dynamics in Lagos State's Coastal Zones - Adedoja, Toyosi; Adegboyega, Suleiman; Fakpor, Akpofure (African Journal of Inter/Multidisciplinary Studies, 2024)
Coastal regions are experiencing rapid urbanization, leading to substantial land use and land cover (LULC) transformations that profoundly impact the environment, livelihoods, and ecosystem services, and this has become a concern for environmentalists. However, research linking dynamics to ecosystem service valuation in this critically important ecoregion is rarely studied. This study attempts to bridge this gap by quantifying the ecosystem services in Lagos, Nigeria's rapidly urbanizing coastal region. A multi-temporal Landsat imagery of 2003, 2013, and 2023 was employed to map LULC categories in the region. Furthermore, the Value transfer method was employed to estimate the ecosystem services in each LULC type. The estimated ecosystem service values revealed significant transitions, with an overall decline of $985.01 million from 2003-2013; built-up areas experienced the most significant increase, rising with $47.06 million, while mangrove forests saw the most significant decline, dropping to $ 602.86 million. Between 2013 and 2023, built-up continue to exhibit the most significant increase in value, with $15.72 million. Conversely, mangroves experienced a sharp decline, decreasing with $153.52 million. The valuation of LULC-associated ecosystem services in Lagos's coastal zone highlights the urgent need to integrate environmental accounting into coastal management.